Effect of combined solifenacin and aclatonium in preventing dry mouth in patients with overactive bladder. Issue 1 (1st October 2017) - Park, Hyoung Keun; Kim, Hyeong Gon; Yang, Dae Yul; Choi, Woo Suk; Paick, Sung Hyun; Chung, Hong; Yang, Sang‐Kuk
Abstract : Objective: The aim of the present study was to prospectively evaluate the effect of aclatonium on dry mouth in patients with overactive bladder (OAB) after treatment with solifenacin. Methods: A multicenter randomized double‐blind controlled trial was conducted. The study subjects were men and women who had been diagnosed with OAB for ≥3 months and presented with a total Overactive Bladder Symptom Score (OABSS) ≥3. Eligible subjects were randomized to receive 5 mg solifenacin with placebo or 5 mg solifenacin with 150 mg aclatonium once daily for 8 weeks. Subjects rated dry mouth using a visual analog scale (VAS) and completed the OAB‐questionnaire (OAB‐q) short form (SF) and OABSS questionnaires at baseline and after 8 weeks treatment. Dry mouth was defined as a VAS score >30 points (range 0–100). Results: Overall, 92 patients (49 and 43 in the placebo and aclatonium groups, respectively) completed the 8‐week treatment. In patients who had dry mouth at baseline, no differences were detected in changes in the dry mouth VAS, OABSS, or OAB‐q SF scores between the 2 groups. However, in patients who had no dry mouth at baseline, the change in dry mouth VAS score was significantly lower in the aclatonium‐ than placebo‐treated group: the VAS score increased 20 points in the placebo group compared with 9 points in the aclatonium group ( P  = .03). However, there were no significant differences in changes in the OABSS and OAB‐q SF scores between the 2 groups. Conclusions: Aclatonium decreased dry mouth without disturbing treatment efficacy in patients who did not have dry mouth before treatment.